Deciphering the tectonometamorphic history of subducted metapelites using quartz‐in‐garnet and Ti‐in‐quartz (QuiG–TiQ) geothermobarometry—A key for understanding burial in the Scandinavian Caledonides. (16th November 2022) - Jeanneret, Pauline; Klonowska, Iwona; Barnes, Christopher; Majka, Jarosław; Holmberg, Johanna; Gilio, Mattia; Nachlas, William; Alvaro, Matteo; Kośmińska, Karolina; Lorenz, Henning; Zack, Thomas; Ladenberger, Anna; et al.
Abstract: The Seve Nappe Complex is a subduction‐related high‐grade metamorphic unit that was emplaced onto the margin of Baltica during Caledonian orogenesis. In this paper, the tectonometamorphic evolution of the Lower Seve Nappe in the Scandinavian Caledonides was characterized with the help of the continuous Collisional Orogeny in the Scandinavian Caledonides (COSC‐1) drill core, using a combination of various P–T estimation techniques based on garnet–quartz mineral pairs (quartz‐in‐garnet and Ti‐in‐quartz [QuiG–TiQ]), conventional thermobarometry and thermodynamic modelling of phase equilibria. This multi‐method approach yields complementary results and delivers critical data to constrain a comprehensive pressure–temperature–deformation–time (P–T–D–t) evolutionary path for the metasedimentary rocks of the Lower Seve Nappe. In the garnetiferous metasedimentary rocks, quartz inclusions in garnet preserve the P–T conditions of three distinct garnet growth stages corresponding to three metamorphic stages Ms1 to Ms3, including prograde and peak metamorphic conditions. Ms1 and Ms2 stages were constrained via quartz inclusions in garnet core and mantle. They are relatively close in the P–T space and could be considered as one single continuous prograde event occurring at epidote–amphibolite facies conditions of 460–520°C and 0.6–0.85 GPa. The growth of the garnet outermost rim defines the Ms3 stage at amphibolite facies conditions of 590–610°C and 1.13–1.18 GPa and corresponds to the peak metamorphic conditions. The microstructural analysis shows that the finite ductile strain pattern of the Lower Seve Nappe results from the superposition of four deformation phases. The initial phase D1 is defined by the S1 foliation that is still preserved as a curved inclusion trail in the garnet core. The D2 phase initiated contemporaneously with garnet core growth and the development of muscovite–biotite–plagioclase S2 foliation. Garnet outermost rim growth marks the end of the prograde path and peak metamorphic conditions. This stage is overprinted by the D3 phase and Ms4 stage associated with the development of the main regional metamorphic and mylonitic fabric S3 associated with C′‐type shear bands along the retrograde path. Ms4 stage, which was constrained using traditional thermobarometric techniques, corresponds to the chemical re‐equilibration of the metasedimentary minerals and occurred under amphibolite facies conditions at ~570–610°C and 0.78–1.00 GPa. The D3 phase is then generally weakly to strongly overprinted by later lower grade deformation D4 phase at greenschist facies conditions (Ms5). 40 Ar/ 39 Ar ages of syn‐kinematic white mica and biotite indicate that the final stage of the thrusting of the Lower Seve Nappe and thus the timing of its emplacement onto the Offerdal Nappe occurred at c. 423 Ma. Collectively, these results are consistent with previous estimates of the timing and conditions of metamorphism derived from the Lower Seve Nappe especially in west‐central Jämtland. However, application of QuiG–TiQ thermobarometry demonstrated that quartz inclusions in garnet can preserve different aspects of garnet growth, which are not accessible by traditional methods especially in complex terranes, and therefore provided new significant insights into the Lower Seve prograde evolution.